1977
DOI: 10.1073/pnas.74.12.5239
|View full text |Cite
|
Sign up to set email alerts
|

Transition state structures of a dipeptide related to the mode of action of beta-lactam antibiotics.

Abstract: The tetrahedral adducts formed during nucleophilic attack by a hydroxyl ion on the carbonyl carbon of a model dipeptide, glycylglycine, were studied by modifiedintermediate-neglect-of-differential-overlap molecular orbital calculations. This dipeptide is taken to represent the D-alanyl-D-alanine terminus of the polypeptides involved in the crosslinking transpeptidation reaction of peptidoglycan in bacterial cell walls. It Twelve years ago it was proposed (1) that the fl-lactam antibiotics derive their antiba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…21 Structureactivity studies 22,23 and the evidence from conformationally restricted penicillin analogues 24 suggested that the more broadly biologically active form has the "open" or "S-puckered" conformation. In particular, evidence from studies with the conformationally restricted penicillins suggested that this form was the more reactive with the R61 DD-peptidase.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…21 Structureactivity studies 22,23 and the evidence from conformationally restricted penicillin analogues 24 suggested that the more broadly biologically active form has the "open" or "S-puckered" conformation. In particular, evidence from studies with the conformationally restricted penicillins suggested that this form was the more reactive with the R61 DD-peptidase.…”
Section: Resultsmentioning
confidence: 98%
“…26 Boyd provided evidence for this idea from computational studies of the relevant structures. 21 Figure 4(c) shows the overlap between the E2 complex and an energy-minimized model of the tetrahedral intermediate for acylation of the R61 DD-peptidase by 1. Interestingly, the similarity between the peptide and b-lactam is more striking in Figure 4(c) than that observed in the crystallographic structures as shown in Figure 4(a), particularly around the reaction center.…”
Section: Resultsmentioning
confidence: 98%
“…In this regard, the Tipper-Strominger hypothesis [67], in other words, that β-lactam antibacterials mimic the conformation of the D-Ala-D-Ala component of the PBP bacterial cell wall substrate, may be relevant [68], in that in order to get to the stage where reaction to the acylenzyme complex can occur the β-lactam antibacterial must efficiently compete with the natural substrate for binding [69]. Following from biophysical evidence that some nucleophilic serine enzymes may bind their substrates in a high-energy conformation which strains the amide bond [70][71][72], a refinement of the Tipper-Strominger hypothesis suggests that (some) β-lactam antibacterials may mimic a strained conformation of the D-Ala-D-Ala entity (Figure 2) [73][74][75]. Thus, (at least some) β-lactam antibacterials may be highly optimized to bind both noncovalently and covalently; following noncovalent binding, they undergo covalent reaction to form an initial acyl-enzyme complex which at least, in some cases, can undergo either covalent fragmentation [52,53,76] or conformational rearrangement [23,52,[55][56][57]59,62,77] to form (a) more stable complexes.…”
Section: Future Science Groupmentioning
confidence: 98%
“…β-Lactam recognition by these enzymes exploits the structural similarity of the β-lactams to the d -Ala- d -Ala substrate motif of these enzymes as first discerned by Tipper and Strominger. Their hypothesis persists as a durable theme in β-lactam structural biochemistry. Chart shows this structural mimicry and compares the structure of an intact and clinically used cephalosporin β-lactam and the β-lactam-opened structure of an inactivated transpeptidase. Scheme gives a rudimentary kinetic scheme, which contrasts the peptidoglycan substrate and the β-lactam as inactivator.…”
Section: Introductionmentioning
confidence: 99%